Dissociation and Intrapelvic Entrapment of a Dual-mobility Polyethylene Component - Fehring, Keith A. (Clin Orthop Relat Res, 2015)
BACKGROUND: Dual-mobility bearings have gained popularity in recent years as a proposed method of reducing the risk of dislocation after primary and revision hip arthroplasties. Intraprosthetic dislocation, defined as dissociation of the smaller femoral head from the larger outer polyethylene head, is a known complication of these designs. Intraprosthetic dislocation typically requires reoperation and revision as closed reduction of intraprosthetic dislocations of these components is not effective. The small femoral head typically remains inside the large diameter acetabular component during intraprosthetic dislocation, thus the diagnosis may be missed if femoral head eccentricity is not identified on radiographs. Intraprosthetic dislocation leads to a free polyethylene bearing which typically stays in the joint space, however in theory, migration of the bearing is possible. CASE DESCRIPTION: We report a case of polyethylene bearing disengagement and intrapelvic entrapment after anterior dislocation of a hip with a modern dual-mobility bearing. The diagnosis of polyethylene component migration to an intrapelvic location was not made until surgery. Isolated acetabular revision of the dual-mobility bearing was performed to correct the instability in this patient. The entrapped polyethylene head was left in its intrapelvic position as retrieval was thought to be more morbid than retention of the component. LITERATURE REVIEW: Intraprosthetic dislocation, with disassociation of the polyethylene bearing from the femoral head, is a known complication of dual-mobility designs. Reports of intrapelvic entrapment of trial femoral heads of conventional hip arthroplasties have been described extensively in the literature. To our knowledge, intrapelvic migration and entrapment of a polyethylene bearing after dislocation of a hip with a dual-mobility implant has not been reported. CLINICAL RELEVANCE: We discuss an implant-specific complication that has not been reported, and surgeons should be aware that this unique complication can occur. Surgeons should recognize the eccentricity of the femoral head on postreduction radiographs so an intraprosthetic dislocation is not missed. Furthermore, surgeons should be aware that intraprosthetic dislocation carries a risk of intrapelvic migration of the polyethylene component which is not visible on plain radiographs.